Partnering with parents in a pediatric ambulatory care setting: a new model. (June 2015) - Tourigny, Jocelyne; Chartrand, Julie
<x xml:space="preserve">Abstract</x> Pediatric care has greatly evolved during the past 30 years, moving from a traditional, medically oriented approach to a more consultative, interactive model. In the literature, the concept of partnership has been explored and presented in various terms, including presence, collaboration, involvement, and participation. The models of partnership that have been proposed have rarely been evaluated, and do not take the unique environment of ambulatory care into account. Based on a literature review, strong clinical experience with families, and previous research with parents and health professionals, both the conceptual and empirical phases of a new model are described. This model can be adapted to other pediatric health care contexts in either primary or tertiary care and should be evaluated in terms of efficacy and usefulness.